Comprehensive Research on the Effects of Different Launch Conditions on Pump-jet Propulsor Performance - Q. Fu; Y. Duan; W. Shi; H. Li; R. Zhu (Journal of Applied Fluid Mechanics)
This paper compares the cavitation of a pump-jet propulsor under different launch conditions and discusses the effects of cavitation on the performance and noise of the pump-jet propulsor rotor blade. At the same time, the load and deformation of the rotor blade under the conditions of cavitation are studied via the one-way fluid-structure interaction (FSI) approach. The results show that the cavitation of the pump-jet propulsor decreases with increasing launch depth and speed. The performance decreases with increasing launch speed at large depths, whereas the performance improves with increasing launch speed at small depths due to the improvement of the cavitation on the rotor blades. Increasing launch speed and depth increase the noise caused by the rotor of the pump-jet propulsor, and the increase in flow rate caused by the improvement of cavitation also increases the noise level. Moreover, increasing launch depth increases the overall load of the blade and produces a larger deformation, while the speed affects the distribution of the load on the blade. In addition, with the improvement of cavitation caused by increasing launch speed, the deformation of the blade decreases.